An Economy of Grace - Chen, Victor Tan (Religions, 2017)
This essay is adapted from a plenary talk the author gave at the Growing Apart: The Implications of Economic Inequality interdisciplinary conference at Boston College on 9 April 2016, as well as portions of his book Cut Loose: Jobless and Hopeless in an Unfair Economy, a sociological ethnography based on interviews and observations of unemployed autoworkers in Detroit, Michigan, and Windsor, Canada, during and after the Great Recession. The essay discusses four themes from this research. First, it provides a sociological understanding of how long-term unemployment and economic inequality are experienced by today's less advantaged workers. Second, it illustrates how social policy can improve their circumstances. Third, it examines the limits of policy, and how dealing with inequality also requires changing the broader culture. Fourth, it makes the case for one possible approach to bring about that cultural change: a morality of grace.